Development of a self-diagnostic system integrated into a cyber-physical system - Oliveira, Domingos F. (2022)
CONTROLAR provides Bosch with an intelligent functional testing machine used to test the correct functioning of the car radios produced. During this process, the radios are submitted to several tests, raising the problem of how the machine detects errors in several radios consecutively, making it impossible to know if the device has a problem since it has no module to see if it works correctly. This article arises from the need to find a solution to solve this problem, which was to develop a self-diagnostic system that will ensure the reliability and integrity of the cyber-physical system, passing a detailed state of the art. The development of this system was based on the design of an architecture that combines the KDT methodology with a DSL to manage and configure the tests to integrate the self-diagnostic test system into a CPS. A total of 28 test cases were performed to cover all its functionalities. The results show that all test cases passed. Therefore, the system meets all the proposed objectives.